Steels microstructure and properties - Bhadeshia, H. K. D. H. 1953- (Elsevier, Butterworth-Heinemann, 2006)
The most comprehensive and up-to-date textbook on the microstructure and properties of steels.
Previous edition: London : Edward Arnold, 1995. Primary author, Honeycombe.
Keywords: Steel.; Steel -- Metallurgy.; Steel -- Metallography.; elektronické knihy; electronic books